Severity of Nausea and Vomiting in Singleton and Twin Pregnancies in Relation to Fetal Sex: The Japan Environment and Children’s Study (JECS) - Naomi Mitsuda; Masamitsu Eitoku; Nagamasa Maeda; Mikiya Fujieda; Narufumi Suganuma (Journal of Epidemiology, 2019)
Background: Some studies have indicated that female birth and multiple births were risk factors for nausea and vomiting during pregnancy (NVP). The results, however, were conflicting. Our study was conducted to evaluate the association of maternal NVP with fetal sex in singleton and twin pregnancies. Methods: We used the data set from a birth cohort study, the Japan Environment and Children’s Study (JECS). In the self-administered questionnaire, participants were asked whether they experienced NVP prior to 12 gestational weeks. Main outcome measures were the presence of NVP and severity of NVP. We estimated the association of fetal sex and birth plurality with NVP using logistic regression analysis, followed by interaction analysis. Results: Of 91,666 women, 75,828 (82.7%) experienced at least some symptoms of NVP and 10,159 (11.1%) experienced severe NVP. Women with female pregnancies and twin pregnancies had higher odds for the presence of NVP and severe NVP compared to women with male pregnancies and singleton pregnancies, respectively. Moreover, of mothers with twin pregnancies, higher odds for the presence of NVP and severe NVP were reported when one or both infants were female, compared to those in which both infants were male. There was no significant interaction between fetal sex and birth plurality. Conclusions: Female sex birth and multiple births are risk factors for the presence of NVP, and especially for severe NVP without interaction. These findings suggest that a factor abundant in the female fetus associates with the severity of NVP.